Variability among Physicians in Risk Stratification for People with Diabetes during Ramadan Fasting - Bachar Afandi; Mohamed Hassanein; Shehla Shaikh; Gamal Ibrahim; Monira Alarouj (Dubai Diabetes and Endocrinology Journal)
Introduction: A novel clinical calculator was developed to assist physicians in classifying the risk for individuals with diabetes planning to observe fasting during the holy month of Ramadan. The aim of this study was to evaluate the necessity to use this approach. Methods: A survey with twenty-six clinical scenario questions was developed. All cases were pre-scored using the proposed Diabetes and Ramadan Risk Calculator. The survey was sent to 350 reputable practicing physicians with considerable expertise in managing patients with diabetes. The survey sought expert opinion on patients’ risk classification during Ramadan fasting. Quantitative methods were used for data analysis. Results: Responses of 312 participants were valid for analysis. There was a wide variation in evaluating patients’ risk, particularly in moderate-risk cases. Overall, responses to case scenarios were classified correctly with 33–85% variation in correct response. Geographical and inter-specialty differences were noted. Conclusion: There is a broad variation among physicians on how to estimate the risk for patients with diabetes planning to fast during the month of Ramadan. A practical method using many variables might help physicians in the decision making.